The effect of school-entry age on health is understudied in low- and middle-income countries: a scoping review and future directions for research - Liao, Janny; Schröder, Henning; Chin, Elliot K.; Bakare, Muideen Owolabi; Moshoeshoe, Ramaele; Caudillo, Mónica L.; Munir, Kerim M.; De Neve, Jan-Walter (SSM - population health, 2023)
Background - Substantive literature has assessed the impact of starting school at younger ages relative to peers on health in high-income countries (HICs), but there is little evidence from low- and middle-income countries (LMICs). Conclusions drawn from HICs may not apply to different education contexts and health threats. This study maps the empirical evidence on the effect of school-entry age on health in LMICs and identifies directions for future research. - Methods - We conducted a scoping review between August and September 2022 by systematically searching the health sciences, education, economics, psychology, and general sciences literature and included quantitative and qualitative studies. The exposure of interest was relative age for grade defined as starting or progressing through school at a younger or older age compared to peers who are in the same grade. We extracted key characteristics of included studies and summarized their findings. We categorized results into broad health domains which emerged a posteriori from our analyses of included studies, including neurodevelopment and mental health, sexual and reproductive health, non-communicable diseases, and nutrition. - Findings - We identified 8 studies from middle-income countries published between 2017 and 2022. Among those studies, we identified 3 quasi-experimental studies using data from Brazil, Mexico, and Vietnam, and 5 observational studies primarily from Türkiye. Children starting school earlier had an increased risk of being diagnosed with attention deficit hyperactivity disorder, earlier sexual debut and cohabitation, adolescent pregnancy, adolescent marriage, and engaged more frequently in risky behavior compared to children who started school later. Pregnant women who started school younger also had fewer prenatal care visits and experienced more pregnancy complications. Although most studies identified negative health consequences from starting school earlier, the evidence for nutritional outcomes, such as overweight and stunting, was mixed. No studies were identified from low-income countries. - Conclusions - Little is known about the health consequences of school-entry age in low-resource settings. Additional research is needed to investigate the impact of relative age for grade, whether and how these effects persist into adulthood, and to inform strategies that can offset potential disadvantages stemming from school-entry cut-off dates.